Selective Hydrogenation of Sucrose into Sugar Alcohols over Supported Raney Nickel-Based Catalysts - Rodiansono Rodiansono; Maria Dewi Astuti; Dwi Rasy Mujiyanti; Uripto Trisno Santoso (Indonesian Journal of Chemistry, 2019)
Selective hydrogenation of sugars (e.g. sucrose, cellobiose, glucose, fructose, xylose, arabinose) into sugar alcohols (sorbitol, mannitol, xylitol, arabitol) can be achieved by means of supported Raney Ni-based catalysts. Various supporting materials such as the layered structure of clay (e.g. bentonite, taeniolite, smectite), metal oxides (e.g. Nb2O5, ZrO2, Al2O3), and conventional supports (e.g. carbon, silica, zeolite (JRC-SZ1)) were employed to obtain high performance of supported Raney Ni-based catalysts. The conventional Raney Ni, Raney Ni/AlOH, and Ni-NP with relatively high dispersion exhibited superior catalytic activity compared with the various supported Raney Ni catalysts with the conversion of 100% and hexitols selectivity almost ~99%. The H2 treatment of Raney Ni/SMT at a temperature of 473–773 K caused the increase in Ni(111) crystallite sizes as the conversion of sucrose with compromised decreased of hexitols product. The presence of acidic co-catalyst such as SnO, amberlyst-15, JRC-SZ1, JRC-Z5-9OH1 on Raney Ni/AlOH catalyst significantly enhanced the formation of glycerol product even though the conversion of sucrose compromised decreased owing to the partial leaching of Ni metal into the reaction mixture.